Eksplorasi Hubungan Antara Fear of Missing Out dan Social Connectedness pada Generasi Milenial - Nurul Huda; Almira Kusumaningrum; Dina Kusuma Astuti (Jayapangus Press, 2026)
Millennials use technology extensively, including excessive smartphone use, which leads to a lack of direct social interaction with their surrounding environment. This issue affects individuals’ social connectedness and results in fear of missing out (FoMO) due to continuous use of social media. The purpose of this study is to empirically examine the relationship between fear of missing out (FoMO) and social connectedness among millennials. The method used in this study is a quantitative method. The sampling technique applied is purposive sampling, and the data analysis used is Pearson product–moment correlation. The researcher used the Social Connectedness Scale based on aspects companionship, affiliation, and connectedness. Meanwhile, the Fear of Missing Out (FoMO) scale was developed based on aspects autonomy, competence, and relatedness. Based on the findings, the hypothesis test obtained a significance value of 0.000 (p < 0.001) with an r value of 0.316. These results indicate that there is a highly significant positive relationship between fear of missing out (FoMO) and social connectedness among millennials.